2020
DOI: 10.4049/immunohorizons.2000068
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-Wide Zika Virus CD4 T Cell Epitope and HLA Restriction Determination

Abstract: Zika virus (ZIKV) is a mosquito-borne pathogen that caused an epidemic in 2015-2016. ZIKV-specific T cell responses are functional in animal infection models, and helper CD4 T cells promote avid Abs in the vaccine context. The small volumes of blood available from field research limit the determination of T cell epitopes for complex microbes such as ZIKV. The goal of this project was efficient determination of human ZIKV CD4 T cell epitopes at the whole proteome scale, including validation of reactivity to who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…This strategy is therefore particularly effective when an educated guess or inference of HLA restriction is available. An alternative methodology is the use of single HLA transfected APCs [102,[130][131][132][133]. In these experiments, the peptide is tested in antigen presentation assays utilizing panels of cell lines expressing single HLA molecules that match an allele expressed in the donor from which the T cell response is generated.…”
Section: Hla Restriction Of Epitope Responsesmentioning
confidence: 99%
“…This strategy is therefore particularly effective when an educated guess or inference of HLA restriction is available. An alternative methodology is the use of single HLA transfected APCs [102,[130][131][132][133]. In these experiments, the peptide is tested in antigen presentation assays utilizing panels of cell lines expressing single HLA molecules that match an allele expressed in the donor from which the T cell response is generated.…”
Section: Hla Restriction Of Epitope Responsesmentioning
confidence: 99%
“…Most of the vaccines against SARS-CoV-2 are in development, under trials or in emergency usage are targeting the humoral immune response for making neutralizing antibodies (Amanat and Krammer 2020 ; Le et al 2020 ). However, the concept of acquired, specific T cell immunity becomes crucial in context of vaccination to clear viral infections and enhance neutralizing antibody responses (Campbell et al 2020 ). Many studies have reported a higher frequency of Spike protein specific CD4 T cell responses and heightened CD8 T cell responses specific to other internal proteins of SARS-CoV-2 in convalescent individuals (Grifoni et al 2020 ; Sekine et al 2020 ; Dong et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the role of CD4 T cell epitope based viral vaccine cannot be overlooked given their ability to enhance activation of CD8 T cell, inducing protective CD8 T cell memory and prolonging their antiviral function (Phares et al 2012 ). Additionally, CD4 T cells also trigger antigen-specific B cells immunoglobulin class switching and affinity maturation (Campbell et al 2020 ).Yet, an exaggerated and distinctive pro-inflammatory response is also reported with reference to severity of COVID-19 disease (Johnson and Laloraya 2020 ). Nonetheless, balance in the pro-inflammatory and anti-inflammatory immune responses determines the outcome of any bacterial or viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…We defined CD4 TCL HLA restriction as published (40). First, serial dilutions of peptide (1, 0.1, or 0.01 μg/ml) were tested in triplicate using autologous EBV-LCL as APC without or with mAbs that block HLA DR, DP, or DQ (100).…”
Section: Methodsmentioning
confidence: 99%
“…First, serial dilutions of peptide (1, 0.1, or 0.01 μg/ml) were tested in triplicate using autologous EBV-LCL as APC without or with mAbs that block HLA DR, DP, or DQ (100). To determine allele-level restriction, engineered APC expressing single HLA class II heterodimers were selected (40) to match the study subject. Negative controls were cells parental to the single antigen line (SAL).…”
Section: Methodsmentioning
confidence: 99%